The Variable Angle Hip Fracture Nail Relative to the Gamma 3: A Finite Element Analysis Illustrating the Same Stiffness and Fatigue Characteristics - Amir Matityahu; Andrew H. Schmidt; Alan Grantz; Ben Clawson; Meir Marmor; R. Trigg McClellan (Advances in Orthopedics)
Ten percent of the 250,000 proximal femur fractures that occur in the United States each year are malreduced into a varus position after treatment. Currently, there is no cephalomedullary nail available that allows the physician to dynamically change the lag-screw-to-nail angle. The Variable Angle Nail (VAN) was designed to allow movement of the lag screw relative to the shaft of the nail. This study compared the characteristics of the VAN to the Gamma 3 nail via finite element analysis (FEA) in stiffness and fatigue. The results of the FEA model with the same loading parameters showed the Gamma 3 and the VAN with lag-screw-to-nail angle of 120° to have essentially the same stiffness values ranging from 350 to 382 N/mm. The VAN with lag-screw-to-nail angles of 120°, 130°, and 140° should be able to withstand more than 1,000,000 cycles from 1,400 N to 1,500 N loading of the tip of the lag screw. The Gamma 3 should be able to last more than 1,000,000 cycles at 1,400 N. In summary, the VAN is superior or equivalent in stiffness and fatigue when compared to the Gamma 3 using FEA.